2020
DOI: 10.1038/s41598-020-79929-0
|View full text |Cite|
|
Sign up to set email alerts
|

Reliance on model-based and model-free control in obesity

Abstract: Consuming more energy than is expended may reflect a failure of control over eating behaviour in obesity. Behavioural control arises from a balance between two dissociable strategies of reinforcement learning: model-free and model-based. We hypothesized that weight status relates to an imbalance in reliance on model-based and model-free control, and that it may do so in a linear or quadratic manner. To test this, 90 healthy participants in a wide BMI range [normal-weight (n = 31), overweight (n = 29), obese (n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…While behavioral patterns present for AN-R are relatively consistent with prior work in psychiatric samples 25,3739,41,44 , the lack of difference between AN-BP and HC was unexpected. A prior study showed that AN displayed attenuated model-based learning compared to HC, with this effect being largely driven by AN-BP 41 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While behavioral patterns present for AN-R are relatively consistent with prior work in psychiatric samples 25,3739,41,44 , the lack of difference between AN-BP and HC was unexpected. A prior study showed that AN displayed attenuated model-based learning compared to HC, with this effect being largely driven by AN-BP 41 .…”
Section: Discussionsupporting
confidence: 77%
“…Reinforcement Learning in Anorexia Nervosa Across psychiatric conditions, there is emerging evidence suggesting that disorders of compulsivity (e.g., obsessive-compulsive disorder, substance use) demonstrate deficits in model-based learning during sequential decision-making 25,[37][38][39][40] . Critically, prior work examining model-based and model-free learning in a mixture of community and clinical samples endorsing symptoms of eating pathology (e.g., compulsive eating), also demonstrate attenuation in modelbased learning 25,[37][38][39]41 . Only one such study was conducted in a sample of individuals with fullthreshold AN and found evidence of deficits in model-based learning for food and money that were not remediated at weight restoration, reflecting a potential trait behavioral marker of the disorder.…”
Section: Reinforcement Learning In Anorexia Nervosamentioning
confidence: 99%
“…Propensity for the habit‐based control system increases an individual's risk for excessive substance use/abuse [72, 73, 110–112], as well as obesity [73–78, 110]. As already discussed, habit‐based control involves slower or no updating of choices when changes in reinforcement occur.…”
Section: Aberrant Satiation: Risk For Compulsive Overeatingmentioning
confidence: 99%
“…Importantly, obesity is characterized by altered dorsal and ventral striatal functioning and an insensitivity to prediction errors [85]. This is not surprising considering the relation between propensity for habit‐based control and obesity [73, 75–77], as habit‐based control is largely insensitive to prediction error.…”
Section: Reinforcement Learning and Decision‐making Systemsmentioning
confidence: 99%
See 1 more Smart Citation